Effect of Recruitment on Employee Performance - Eva Yanti; Intan Rahmayuni Syafitri; Taufik Hendra; Sufyarma Marsidin; Nellitawati Nellitawati; Prozoe Rezo (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
Employees are the most important part to achieve the goals of a company or organization. So that the company runs effectively and efficiently, the company needs employees who are in accordance with the principle of "the right man in the right office". To achieve the goals of the company or organization, the first step taken is to recruit prospective employees according to the qualifications of the company or organization, which will improve employee performance results while in a company or organization.